Road User Perception of Street Lighting and Traffic Signs: A Case of Jalan Jaka Kusuma - Intannia Wandhani; Mohamad Taufik; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2025)
Road lighting and traffic signs are essential in ensuring traffic safety. Adequate road lighting and traffic signs can create a sense of security and comfort for road users. Conversely, the lack of lighting and traffic signs can create discomfort or even increase the risk of danger and crime on the road. In this case, the case on one of the roads in Jatitujuh had inadequate road lighting and traffic signs, causing road users to feel uncomfortable when driving. This study examines the perceptions of road users in Jalan Jaka Kusuma towards road lighting and traffic signs and their impact on driving safety. The research location was conducted on one of the roads in Jatitujuh, Majalengka, West Java, more precisely on Jalan Jaka Kusuma, Desa Panongan - Jatitujuh. Perceptual analysis is the qualitative methodology used in this study. Respondents' level of importance and satisfaction with street lighting and traffic signs were measured from not important to extremely important and from not satisfied to very satisfied on a scale of 1 to 5. The Importance Performance Analysis (IPA) approach was used to process the data. The 40 respondents' data was split up according to their age, gender, and the type of vehicle they were using to cross the Jalan Jaka Kusuma-Jatitujuh. The questionnaire results show that the men and women who cross Jaka Kusuma road are 50% each; most people who cross Jalan Jaka Kusuma are ≤ 20 years old, and most vehicles used are motorbikes. The results showed that road users' perceptions of the level of importance of street lighting and traffic signs averaged 4.94, which indicates very importance, while its performance only reached an average of 2.39, which means it requires improvement; there is a gap of -2.55 between interests and satisfaction.